A Translation Analysis of Indonesian Verbs and Verb Phrases into English in Maryam Novel into The Outcast by Nurhayat Indriyanto and Makna Sinatria - Putri, Monik Karina; , Dr. Dwi Haryanti, M. Hum; , Mauly Halwat Hikmat, Ph. D (2015)
The research paper analyzes Indonesian verbs and verb phrases in Maryam novel and its translation. The aims of the study are identifying the translation shift variations of verbs and verb phrases and describing the translation quality in Maryam novel into The Outcast. The type of this research paper is descriptive qualitative research. The data of this study are clauses and sentences containing verbs and verb phrases found in Maryam novel. Data sources used in this research are the documentation of the data and the informants. The researcher uses document, questionnaire, and interview the raters in collecting data. The data are analyzed by using comparing method. The results of the research show that from 1079 data of translations shift variations of verbs and verb phrases there are 245 data or 22,70% verb is translated into verb, 13 data or 1,20% verb is translated into noun, 5 data or 0,46% verb is translated into preposition, 2 data or 0,18% verb is translated into adverb, 5 data or 0,46 verb is translated into adjective, 1 datum or 0,09% verb is translated into conjunction, 373 data or 34,56% verb is translated into verb phrase, 19 data or 1,76% verb is translated into noun phrase, 4 data or 0,37% verb is translated into preposition phrase, 1 datum or 0,09% verb is translated into adverb phrase, 59 data or 5,46% verb is translated into clause, and 105 data or 9,90% verb is not translated. Therefore, there are 103 data or 9,46% verb phrase is translated into verb phrase, 3 data or 0,27% verb phrase is translated into noun phrase, 74 data or 6,85% verb phrase is translated into verb, 5 data or 0,46% verb phrase is translated into noun, 33 data or 3,05% verb phrase translated into clause, and 29 data or 2,68% verb phrase is not translated. Moreover, the translation quality score is 2,97. It belongs to high quality translation.